# Algebra

Solve by using the quadratic formula.
3x^2=11x+4.

Look up the formula if you don't know it already.

In this case a = 3, b = -11 and c = -4.

You get that by rewriting the equation in the standard form ax^2 + bx + c = 0 , where a, b, and c are constants.

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### algebra

Unit 4: Quadratic Functions and Equations Lesson 6: The Quadratic Formula and the Discriminant 1.) a=5, b=9, c=-4 2.) C 3.) No solution 4.) x=-2, x=1.25 5.) x=-9, x=3 6.) quadratic formula 7.) 2 8.) 11cm by 16cm

2. ### math help how do i do this

Decide which part of the quadratic formula tells you whether the quadratic equation can be solved by factoring. −b b^2 − 4ac 2a Use the part of the quadratic formula that you chose above and find its value, given the following

3. ### algebra1

what formula should i use to solve this quadratic formula? 2x2 + 4x + 2 = 0.

4. ### Maths

solve the following using quadratic formula 2x^2 - 11x 12=0?

1. ### Algebra

m^2-5m-14=0. Solve using quadratic formula. Thanks.

2. ### Algebra

Use the quadratic formula to solve the equation. Give exact answers. 2x^2 + 11x - 21 = 0 a) -3/2, 7 b) 3/2, -7 c) 3/2, 7 d) -3/2, -7 I could not get any of these answers.

3. ### Math

a) Explain the relationship between the axis of symmetry and the quadratic formula. b) We know that the quadratic formula can be used to determine the roots of a quadratic function. However, the quadratic formula also reveals how

4. ### algebra

Solve this quadratic equation using the quadratic formula. x^2 + 8x - 5 = 0

Solve the following quadratic by either factoring or using the quadratic formula: 6x2 - 5x = 6 6x^2 -5x -6 = 0 (3x+2)*(2x-3) = 0 Take it from there